Nephrectomy Versus Embolization of Non-Functioning Renal Graft: A Systematic Review with a Proportional Meta-Analysis - Takase, Henrique Mochida [UNESP]; Contti, Mariana Moraes [UNESP]; Nga, Hong Si [UNESP]; Bravin, Ariane Moyses [UNESP]; Valiatti, Mariana Farina [UNESP]; El-Dib, Regina Paolucci [UNESP]; Modelli de Andrade, Luis Gustavo [UNESP] (Int Scientific Literature, Inc, 2018)
There is no standardization on the timing of the best approach to treat a non-functioning renal graft. We reviewed the literature and performed a proportional meta-analysis of case series of transplantectomy and embolization for a non-functioning renal graft. The groups were compared for mortality and morbidity outcomes. A total of 2421 patients were included in this review. Of these, 2232 patients underwent transplantectomy and 189 underwent percutaneous embolization. The mortality rate in the nephrectomy group was 4% [95% confidence interval [CI], 2-7%; I-2= 87%] as compared with 0.1% [95% CI, 0.1-0.5%; I-2= 0%] in the embolization group. The rates of common morbidities were 18% [95% CI, 13-26%, I-2= 79.7%] for nephrectomy compared with 1.2% [95% CI, 0.7-2.1%, I2= 26.4%] for embolization. The incidence of post-embolization syndrome was 68%, and 20% of patients needed post-embolization nephrectomy. Percutaneous embolization was associated with lower mortality and morbidity rates but also with a high rate of post-embolization syndrome. However, in most cases this complication had easily manageable symptoms. Embolization is a new and attractive technique that can be considered in treating non-functioning renal grafts.
Keywords: Kidney Transplantation; Nephrectomy; Radiography; Radiology, Interventional